2016
DOI: 10.1111/1751-2980.12324
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal tuberculosis and Crohn's disease: challenging differential diagnosis

Abstract: Along with epidemiological changes in tuberculosis (TB) and an increased incidence of Crohn's disease (CD), the differential diagnosis of intestinal TB (ITB) and CD is of vital importance and has become a clinical challenge because treatment based on misdiagnosis may lead to fatal outcomes. In this study, we reviewed the similarities and differences in clinical, endoscopic, radiological and histological features of these two diseases. Concomitant pulmonary TB, ascites, night sweats, involvement of fewer than f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 61 publications
1
40
0
5
Order By: Relevance
“…In most cases, ITB can be cured with proper anti-TB drugs with a favorable outcome, while CD is a chronic disease needing lifelong management. Moreover, the misdiagnosis of ITB as CD can lead to worse outcomes, because immunosuppressive drugs, such as corticosteroids, thiopurines, and anti-tumor necrosis factor agents can aggravate ITB[ 14 ]. Conversely, the misdiagnosis of CD as ITB can render the CD patients exposed to the potential toxicity of anti-TB drugs and delay the proper treatment of CD.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, ITB can be cured with proper anti-TB drugs with a favorable outcome, while CD is a chronic disease needing lifelong management. Moreover, the misdiagnosis of ITB as CD can lead to worse outcomes, because immunosuppressive drugs, such as corticosteroids, thiopurines, and anti-tumor necrosis factor agents can aggravate ITB[ 14 ]. Conversely, the misdiagnosis of CD as ITB can render the CD patients exposed to the potential toxicity of anti-TB drugs and delay the proper treatment of CD.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of combined detection was improved compared to the single detection sensitivity, but the specificity declined. Discussion differentiate [18] . Some studies have proposed certain criteria for identifying CD and ITB, but these criteria have been shown to have great limitations [19][20][21] .…”
Section: Detection Of Mtbc By Intestinal Tuberculosis Protein Combinementioning
confidence: 86%
“…In some countries where infections are endemic, health care providers might simply assume that abdominal symptoms are due to infections or TB without performing endoscopy. It was reported that the misdiagnosis rates between CD and ITB ranged from 50 to 70% [26] .…”
Section: Diversity Of Diagnostic Qualitymentioning
confidence: 99%